Study of tyramine-binding mechanism and insecticidal activity of oil extracted from Eucalyptus against Sitophilus oryzae - Zargari, Farshid; Nikfarjam, Zahra; Nakhaei, Ebrahim; Ghorbanipour, Masoumeh; Nowroozi, Alireza; Amiri, Azam (Frontiers in Chemistry, 2022)
The rice weevil, Sitophilus oryzae (L.), is a major pest of stored grains throughout the world, which causes quantitative and qualitative losses of food commodities. Eucalyptus essential oils (EOs) possess insecticidal and repellent properties, which makes them a potential option for insect control in stored grains with environmentally friendly properties. In the present study, the binding mechanism of Tyramine (TA) as a control compound has been investigated by funnel metadynamics (FM) simulation towards the homology model of Tyramine1 receptor (TyrR) to explore its binding mode and key residues involved in the binding mechanism. EO compounds have been extracted from the leaf and flower part of Eucalyptus camaldulensis and characterized by GC/MS and their effectiveness has been evaluated by molecular docking and conventional molecular dynamic (CMD) simulation towards the TyrR model. The FM results suggested that Asp114 followed by Asp80, Asn91, and Asn427 are crucial residues in the binding and the function of TA towards TyrR in Sitophilus Oryzae. The GC/MS analysis confirmed a total of fifty-four and thirty-one constituents in leaf and flower, respectively, where most of the components (29) are common in both groups. This analysis also revealed the significant concentration of Eucalyptus, and α‐Pinene in leaves and flowers EOs. The docking followed CMD was performed to find the most effective compound in Eucalyptus EOs. In this regard, Butanoic acid, 3-methyl-, 3-methyl butyl ester (B12) and 2-Octen-1-ol, 3,7-dimethyl- (B23) from leaf, and trans- β‐Ocimene (G04) from flower showed the maximum dock score and binding free energy, making them the leading candidates to replace Tyramine in TyrR. The MM-PB/GBSA, and MD analysis proved that the B12 structure is the most effective compound in inhibition of the TyrR.